Subtitling Translation Strategy and Semiotic Approach on Titanic Film - Ni Made Sila Ulati; Mirsa Umiyati; Agus Darma Yoga Pratama (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
This research is entitled â€œSubtitling Translation Strategy and Semiotic Approach on Titanic Filmâ€. This research aims to identify and analyze the subtitling translation strategies in the Titanic film. This research also analyzes the meaning in Titanic film delivered through non-verbal signs. This research contributes to fill some gaps in the field of film subtitling from English into Indonesian and utilizes the multimodal transcription to deliver the meaning of Titanic film. This research refers to the theory of subtitling strategy by Gottlieb (1992) and the theory of Multimodal Transcription by (Forceville, 2007). The methodology applied in this research is descriptive qualitative due to the analysis in the form of elaboration. This research shows the subtitling translation strategy found in the Titanic film are eight strategies which cover expansion strategy, paraphrase, transfer, imitation, transcription, condensation, decimation, and deletion strategy. The meaning delivered through nonverbal signs in the Titanic film is sadness, the happiness of love, and an unforgettable dreadful tragedy. This meaning is delivered along with the visual images and the soundtrack.